CLINICAL AND PATHOPHYSIOLOGICAL FEATURES OF THE DEVELOPMENT OF ISCHEMIC HEART DISEASE IN PATIENTS WITH DIABETES MELLITUS (Global Conference on Medical and Health Sciences, 2026)
Diabetes mellitus is one of the most pressing problems of modern medicine and represents a significant risk factor for the development of cardiovascular diseases. According to the World Health Organization, patients with diabetes mellitus have a significantly higher risk of developing cardiovascular diseases, particularly ischemic heart disease, which is one of the leading causes of disability and mortality worldwide.
Keywords: diabetes mellitus, including chronic hyperglycemia, lipid metabolism disorders, oxidative stress